Properties of a trapped multiple-species bosonic mixture at the infinite-particle-number limit: a solvable model - Alon, Ofir E.; Cederbaum, Lorenz S. (The journal of chemical physics, 2024)
We investigate a trapped mixture of Bose-Einstein condensates consisting of a multiple number of P species. To be able to do so, an exactly solvable many-body model is called into play. This is the P-species harmonic-interaction model. After presenting the Hamiltonian, the ground-state energy and wavefunction are explicitly calculated. All properties of the mixture’s ground state can, in principle, be obtained from the many-particle wavefunction. A scheme to integrate the all-particle density matrix is derived and implemented, leading to closed-form expressions for the reduced one-particle density matrices. Of particular interest is the infinite-particle-number limit, which is obtained when the numbers of bosons are taken to infinity while keeping the interaction parameters fixed. We first prove that at the infinite-particle-number limit all the species are 100% condensed. The mean-field solution of the P-species mixture is also obtained analytically and is used to show that the energy per particle and densities per particle computed at the many-body level of theory boil down to their mean-field counterparts. Despite these, correlations in the mixture exist at the infinite-particle-number limit. To this end, we obtain closed-form expressions for the correlation energy, namely, the difference between the mean-field and many-body energies, and the depletion of the species, i.e., the number of particles residing outside the condensed modes, at the infinite-particle-number limit. The depletion and the correlation energy per species are shown to critically depend on the number of species. Of separate interest is the entanglement between one species of bosons and the other P − 1 species. This quantity is governed by the coupling of the center-of-mass coordinates of the species and is obtained by the respective Schmidt decomposition of the P-species wavefunction. Interestingly, there is an optimal number of species, here P = 3, where the entanglement is maximal. Importantly, the manifestation of this interspecies entanglement in an observable is possible. It is the position-momentum uncertainty product of one species in the presence of the other P − 1 species, which is derived and demonstrated to correlate with the interspecies entanglement. All in all, we show and explain how correlations at the infinite-particle-number limit of a trapped multiple-species bosonic mixture depend on the interactions and how they evolve with the number of species. Generalizations and implications are briefly discussed.